Spatial changes in the infaunal community of a macrotidal flat in Bahía San Julián, Southern Patagonia, Argentina - Martin, Juan P.; Sar, Alicia; Caminos, Carlos (Revista de Biología Marina y Oceanografía, 2019)
The soft-bottom macrobenthos of Bahía San Julián intertidal was surveyed to identify infaunal assemblages and analyze their relationships with the main environmental factors determining species distribution. Four seasonal surveys (summer, autumn, winter and spring) were performed in the middle and lower intertidal levels at seven sampling stations established on both sides of an urban sewage discharge point, and water and sediment variables were measured. To explore possible spatial variations in the community, environmental and biological data were analyzed using univariate and multivariate statistics. Community composition varied with intertidal level, sediment characteristics and distance to sewage discharge site. In sediment with high mud content, the community was characterized by Darina solenoides, Mysella patagona, Eteone sculpta, Scolecolepides uncinatus and Capitella sp., in the middle intertidal, and was characterized by M. patagona and Ampelisca sp. in the lower intertidal. In sediment with dominance of fine sand, the community was characterized by Aricidea sp. at both intertidal levels. Near the effluent discharge site, the community was largely dominated by M. patagona. Intertidal level and sediment particle size are the main factors determining the composition of benthic assemblages in the study area. Sewage discharge also affects the composition of the infaunal community, possibly as a result of the contribution of particulate organic matter in suspension that stimulates the populations of detritus feeders.